2021
DOI: 10.1371/journal.pgen.1009948
|View full text |Cite
|
Sign up to set email alerts
|

Polycomb repressive complex 2 in adult hair follicle stem cells is dispensable for hair regeneration

Abstract: Hair follicle stem cells (HFSCs) are multipotent cells that cycle through quiescence and activation to continuously fuel the production of hair follicles. Prior genome mapping studies had shown that tri-methylation of histone H3 at lysine 27 (H3K27me3), the chromatin mark mediated by Polycomb Repressive Complex 2 (PRC2), is dynamic between quiescent and activated HFSCs, suggesting that transcriptional changes associated with H3K27me3 might be critical for proper HFSC function. However, functional in vivo studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Premature epidermal barrier development, ectopic Merkel cell formation, and postnatal hair follicle developmental hurdle Dauber et al 129 Decreases the proliferation of hair follicle progenitor cells Perdigoto et al 130 Cannot induce HFSCs activation or fate switch; epidermal pigmentation Cohen et al 131 Flora et al 132 Li et al 133 Haematopoiesis Haematopoiesis defects Lessard et al 141 Increasing susceptibility to hematologic malignancies of EED heterozygous mutants Majewski et al 144 Neonatal pale and hypocellular Xie et al 138 Perturbs the BM HSCs differentiation into restricted lineage progenitor cells Yu et al 112 Ueda et al 143…”
Section: Skin and Hair Follicle Morphogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…Premature epidermal barrier development, ectopic Merkel cell formation, and postnatal hair follicle developmental hurdle Dauber et al 129 Decreases the proliferation of hair follicle progenitor cells Perdigoto et al 130 Cannot induce HFSCs activation or fate switch; epidermal pigmentation Cohen et al 131 Flora et al 132 Li et al 133 Haematopoiesis Haematopoiesis defects Lessard et al 141 Increasing susceptibility to hematologic malignancies of EED heterozygous mutants Majewski et al 144 Neonatal pale and hypocellular Xie et al 138 Perturbs the BM HSCs differentiation into restricted lineage progenitor cells Yu et al 112 Ueda et al 143…”
Section: Skin and Hair Follicle Morphogenesismentioning
confidence: 99%
“…Loss of both PRC1/2 complexes in EpSCs leads to the key epidermal lineage TFs such as P63 and SATB1 being significantly down‐regulated in EpSCs, indicating functional redundancy between PRC1 and PRC2 in the maintenance of epidermal stem cell identity. Moreover, EED absences in adult hair follicle stem cells (HFSCs) cannot induce HFSCs activation or fate switch 132 . In contrast, loss of EED function in adult epidermal stem cells results in epidermal pigmentation 133 .…”
Section: Eed Functions In Ontogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…26 In recent years, some studies have shown that lysine methyltransferases and lysine demethylases exert functions in the proliferation and differentiation of HFSCs. [27][28][29] Therefore, in order to screen key histone methylation-related enzymes that play a role in the proliferation and differentiation of HFSCs, we downloaded the RNA sequencing dataset GSE109574 from the GEO database, which contained 3 HFSCs in quiescent period and 4 HFSCs in growth period. To further identify the key genes involved in HFSC growth and wound healing, we performed differential analysis on the RNA sequencing dataset GSE89928 containing HFSCs samples from 5 controls and 2 skin-injured mice.…”
Section: Lsd1 Interacts With Hsp90 To Enhance the Stability Of The Tr...mentioning
confidence: 99%
“…However, despite the role of PRC2 in hair follicle self-renewal, as previously discussed, genome-wide transcriptional studies in adult hair follicular stem cells have demonstrated that PRC2 does not alter the homeostatic hair cycle, and in quiescent cells does not promote fate switch. Therefore, PRC2 and H3K27me3 play a non-instructive role in this context, and there may be redundant or alternate mechanisms acting to preserve hair follicle stem cell functions and fate maintenance [ 178 ].…”
Section: Pcg Protein Functions and Cell Fate Determinationmentioning
confidence: 99%